Understanding the Communication Strategy of Women's Rights Protection in the Digital Era through Website - Zinaida, Rahma Santhi; Havivi, Siti Lady (Jurnal The Messenger, 2019)
The National Commission on Violence Against Women in Indonesia through their website, release that there are three women who become victims of sexual violence every two hours.  Kalyanamitra  was chosen as the subject of the study because there are not many  NGO s committed in protecting women's rights in Indonesia that have survived for more than 33 years. This study aims to explain how the  communication strategy has been done in this organization through their official website.  The important of  doing this study is that can inspire other  NGO s to optimize the use of online media. The theories  used in this study  are Media Rich Theory (MRT). This study  use interpretative paradigm  with the type of research is qualitative  descriptive. Data were collected by using content analysis from website https://www.kalyanamitra.or.id/#. As the result,  Kalyanamitra  has done effective communication strategy by using techniques such as canalizing, informative, persuasive, and also educative.